A Plea for Critical Changes to the Electronic Medical Record - Braid, M. Ted (Telehealth and Medicine Today, 2018)
The electronic medical record (EMR) is significantly more than a digitalized format for converting patient data into easily stored and recalled information. Today, each patient’s EMR is a vast, growing accumulation of health data sourced from physicians and professional medical devices. And, according to HIPAA, it is the absolute property of the patient. At its best, the EMR is a trusted data source that contributes to improved patient care. It is my concern that in its current state and considering existing legislation, the very thing we are building will fall in upon itself long before its potential is realized. It must change or the promise of national access to critical care data in the emergency department (ED), for example, may never be realized.